The Future of Leadership Addressing Complex Global Issues (Springer International Publishing, 2018)
This book deals with leadership trends in the next decade and beyond. It critically examines how knowledge management can be used to address emerging societal and business issues, such as sustaining complex product quality, controlling automation generated unemployment, increasing cyber insecurity in virtual workforce environment, and unstable government and market trends. These issues require unique leadership qualities to be effective in extremely challenging business and socio-political environments. Included among the topics explored by the authors in this book are: investment for the development of diverse human capital, use of data analytics for performance improvement, declining demographic dividends in population deficient areas, and globally increasing women and minority education and employment. Scholars in business and economics, and managers in industry and government will find this book to be a valuable resource in exploring new directions for the future development of leadership.